An overview of water quality regulation or standards in swimming pools, drinking water, and hot springs in Germany, Canada, and Colombia (2022)
This article presents the regulations in the quality of water in swimming pools and drinking water in Germany, Canada, and Colombia, with a comparison to existing regulations and standards of quality of hot springs. Canada, Germany, and Colombia stipulate that drinking water must be free from unsafe levels of substances chemicals and pathogens, specifying guidelines for the microbiological and chemical parameters. However, in the case of hot springs Canada and Germany do not possess specific regulations or standards, but apply the same microbial and chemical requirements for swimming pools according to Public Swimming Pools Regulation of Canada and the standard DIN 19643 as well as the Infection Protection Act of Germany. Colombia does not have regulations or standards pertaining to the quality of hot springs, as established in article 6 of Decree 554 of 2015, and it does not apply the swimming pool regulations to hot springs.